Economic resilience of Japanese nuclear host communities: A quasi-experimental modeling approach. (October 2019) - Plummer, Paul; Yamamoto, Daisaku
The recent Fukushima disaster has raised policy concerns regarding the resilience of Japan's nuclear host communities. Drawing on concepts from evolutionary economic geography and using a quasi-experimental research design we evaluate how these communities "bounce back, " absorb, and adapt to both unanticipated "shocks" and public-private policy interventions. The experience of two nuclear host communities, Kashiwazaki and Kariwa, relative to their "twin" non-host communities of Sanjo and Izumozaki suggests that long-run developmental trajectories were only temporarily shifted during the nuclear power plant construction phase. This raises questions about the economic justification of nuclear power plants made on the ground of long-term structural transformation of host communities.